Pengaruh Perceived Ease Of Use Terhadap Behavior Intantion Melalui Perceived Enjoyment Sebagai Mediasi Penggunaan Dana E-Wallet di Pontianak - Feryanto, Noser; Octaviani, Dina (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
Advances in information technology in Indonesia continue to grow, resulting in new innovations in the financial sector. One of these innovations is the electronic payment facility (e-wallet) which is experiencing rapid growth and is the main choice for the people of Indonesia. This study aims to examine the effect of perceived ease of use on behavioral intent through perceived enjoyment in digital payments. The sample used was 120 respondents who were DANA e-wallet users. Which is determined using nonprobability sampling techniques, namely purposive sampling and analyzed using Partial Least Square with the help of WarpPLS Software. The results showed that perceived ease of use had a positive influence on behavioral intent. In addition, perceived ease of use also has a positive effect on perceived enjoyment, and perceived enjoyment also has a positive influence on behavioral intention